Smart Teams : How to Move from Friction to Flow and Work Better Together - Crowley, Dermot (John Wiley & Sons, 2023)
Learn how your team can communicate, congregate and collaborate more effectively than ever Smart Teams will help your team to go beyond personal productivity to build a culture where productivity thrives. This book shows you how to turn around the unproductive team behaviours that create friction. You'll learn the 'superproductive' behaviours that promote flow and the most impactful productivity principles for working better together. Smart Teams shares the practical guidelines and key skills you need to lead a productive, cooperative team. Email noise, unproductive meetings and poorly organised projects can stifle creativity and disrupt everyone's workflow. A culture that isn't productive results in long hours, more stress, and a lack of balance. But by raising awareness of how our behaviours impact our work and our colleagues, you build the desire and capability to change within your team. This book is packed with tips, guidelines and expert insights for leaders and managers at any level. Foster a culture of 'superproductivity' Create a set of Smart Team principles to guide cooperation Run fewer, shorter and more effective meetings Collaborate more productively on projects Reduce urgency, interruptions and email noise People want their work to matter, they want to make an impact and they want to do it all with a healthy work-life balance. Productivity is the key to making it all happen! Smart Teams shows you how to implement the culture shift that will allow your team to flourish. This book is part of the Smart Productivity series, helping readers find practical solutions for better managing their time, energy and focus.